Attitudes towards those bereaved by a suicide: a population-based, cross-sectional study in rural Japan - Yamaji Masako; Motohashi Yutaka; Minamizono Sachiko; Kaneko Yoshihiro (BMC, 2008)
Abstract Background Family or friends bereaved by suicide are at risk of experiencing complications because of attitudes regarding suicide. It is important that individuals close to those grieving after a death by suicide demonstrate adequate knowledge and compassionate attitudes. To this end, we examined the factors that contribute to attitudes toward persons bereaved by the suicide of a family member or friend, and perceptions of suicide prevention and the promotion of mental health. Methods A total of 5154 residents of a rural town in northern Japan aged 30-69 years completed a cross-sectional questionnaire. The questionnaire gathered data about demographic variables, depressive symptoms, and issues related to suicide including personal experience of an acquaintance's suicide, attitudes towards those bereaved by suicide, and perceptions regarding suicide prevention. Factors related to these attitudes and perceptions were analysed using logistic regression models. Results Overall, 67.5% of respondents demonstrated appropriate attitudes towards those bereaved by suicide; 30.4% of responses were undetermined, and 2.1% were inappropriate. Undetermined attitudes were associated with male gender (adjusted OR 1.42, 95%CI = 1.26-1.61), younger age (2.64, 2.12-3.29), lower education level (1.32, 1.07-1.62), greater severity of depression (3.81, 2.80-5.20), and lack of personal experience of an acquaintance's suicide (1.39, 1.22-1.57). Inappropriate attitudes were associated with male gender (adjusted OR 1.98, 95%CI = 1.33-2.94), lower education level (2.55 1.34-4.83), and greater severity of depression (6.93, 3.52-13.67). Overall, 16.0% demonstrated passive thoughts regarding suicide prevention and the promotion of mental health in the community, and were associated with male gender (1.22, 1.04-1.42), younger age (2.72, 2.03-3.65), lower education level (1.32, 1.02-1.71), and greater severity of depression (4.94, 3.58-6.82). Conclusion Factors that contributed to undetermined attitudes included male gender, younger age, lower education level, greater severity of depression, and lack of personal experience of an acquaintance's suicide. Passive thoughts regarding suicide prevention and the promotion of mental health were associated with male gender, younger age, lower education level, and greater severity of depression.